A experiência eleitoral da Arena (Aliança Renovadora Nacional) no Estado do Espírito Santo nas eleições de 1974: os casos dos municípios de Cachoeiro de Itapemirim, Colatina e Vitória - Duarte, Bruno Sobroza (2014)
This present dissertation has as its object-problem the of ARENA (Aliança Renovadora Nacional) in the State of Espírito Santo, its organization and its 1974 electoral experience, especially the municipalities election results in Vitória, Cachoeiro de Itapemirim and Colatina, municipalities of great importance for the State of Espírito Santo due to its population and electoral numbers. But more than that, because they are in different geographical and strategical points, which make them a source of analysis of propicious data for a possible reading of what was happening throughout the State of Espírito Santo and besides, for having important portionsof Capixabas Elites, which lead to disputes in these regions generate impacts on the geopolitics of the State of Espírito Santo. The year of 1974 had a huge importance in the national scene due to electoral turn of the MDB that represented the beginning of the end of the military regime, facing due to this identification of Brazilian Society with MDB that came to be seen as a way of putting against the regime. Added up to the victories of MDB in all the country, came the rise of the party politics identification that has reached new heights. but in the case of the State of Espírito Santo, there was no mechanical reproduction of that scene. In the Espírito Santo, the transfer of votes for the MDB did not occur, so, the Capixaba population did not incorporate this kind of protest of the Brazilian Society against the direction taken in the country by the conduction of the regime. In the 1974 election, even though, MDB elected a candidate to the Senate, The Federal Deputy Dirceu Cardoso, the election result in Espírito Santo showed, once more time, widely favorable to ARENA and the MDB victory by the candidate to the Senate did not represent the MDB victory but the victory of Dirceu Cardoso, ex-PSD, a closer person to the ARENA leadership than his ARENA opponent, José Carlos da Fonseca. Therefore, Studying the 1974 election in the State of Espírito Santo means respond the hypothesis that the victory of the MDB is more a result of the internal division of ARENA than a protest from the Capixaba society or a political turn against the Military Regime.